The Relationship Between Negative Focused Disposition and Suicidal Ideation Among College Students: The Mediating Effects of Somatic Anxiety, General Distress, and Depression - Sun, Guoxiao; Liu, Zongyu; Ma, Zhiyao; Lew, Bob; Jia, Cunxian (Frontiers in Psychiatry, 2022)
Objective Suicide among college students is a major public health problem. Research has confirmed that negative focused disposition had a significant effect on suicidal ideation. This study aims to evaluate somatic anxiety, general distress and depression as mediators of the relationship between negative focused disposition and suicidal ideation. Methods A total of 1798 college students (942 males) were recruited to complete measures of negative focused disposition, somatic anxiety, general distress, positive affect and suicidal ideation. The mediation models were conducted to assess the mediating effects of somatic anxiety, general distress and depression. Results There was a significant and positive correlation between negative focused disposition and suicidal ideation in Chinese college students. On mediation analysis, somatic anxiety, general distress and depression mediated the relationship between negative focused disposition and suicidal ideation. Conclusions Negative focused disposition appears to directedly associate with suicidal ideation and can indirectly relate to suicidal ideation through the relation with somatic anxiety, general distress and depression. College students with few positive expectations of the future may benefit from interventions focusing on somatic anxiety, general distress and depression.